A Framework Illustrating Care-Seeking Among Older Adults in a Hospital Emergency Department. (17th June 2017) - Lutz, Barbara J; Hall, Allyson G; Vanhille, Sean B; Jones, Andrea L; Schumacher, Jessica R; Hendry, Phyllis; Harman, Jeffrey S; Carden, Donna L
Abstract: Background and Objectives: Older adults seeking emergency department (ED) care often have multiple, complex chronic conditions. We sought to understand factors that influence ED care-seeking by older adults and present a theoretical framework illustrating this process. Research Design and Methods: In this grounded theory study, we interviewed 40 older adults with chronic illness within 90 days of an ED visit to explore their decision-making about seeking ED care. We also interviewed 10 primary care and ED physicians to explore conditions that influence ED referrals. Interview transcripts were analyzed using constant comparison and dimensional analysis. Results: ED care-seeking among older adults is complex and influenced by multiple internal and external conditions including symptom type, severity, and onset; previous experience with and meaning of similar symptoms; limited access to prompt primary care; social and financial concerns; and deciding if symptoms warranted immediate attention. When contacting their primary care providers (PCPs), patients were often referred to the ED. Discussion and Implications: Older adults seeking ED care make rational and appropriate choices which are often predicated by referrals from their PCPs. Expecting patients to have the requisite knowledge to determine if symptoms require emergency care is unrealistic. ED visits are often the best strategy for patients to receive appropriate care. A healthcare system that provides better continuity between PCPs and the ED, better access to PCPs for urgent care, and timely follow-up care that takes into account the multiple and complex medical and social needs of older community-living adults is needed.